2000
DOI: 10.1046/j.1523-1755.2000.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of cytoplasmic VEGF to the basolateral aspect of renal tubular cells in ischemia-reperfusion injury

Abstract: Although synthesis of VEGF mRNA and protein is not increased during ischemia reperfusion injury, pre-existing VEGF in the tubular cell cytoplasm redistributes to the basolateral aspect of the cells. These data suggest that the kidney may have evolved unique patterns of VEGF regulation to cope with acute hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 43 publications
7
46
1
1
Order By: Relevance
“…However, human cell lines were demonstrated recently to present decreased expression levels of HO-1 under hypoxia, with protein Bach-1 being implicated as a hypoxia-inducible repressor for the HO-1 gene (25). In addition, a peculiar response to experimental hypoxia has been demonstrated in the kidney, which may redistribute the pre-existing VEGF protein, rather than increase mRNA and protein synthesis (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, human cell lines were demonstrated recently to present decreased expression levels of HO-1 under hypoxia, with protein Bach-1 being implicated as a hypoxia-inducible repressor for the HO-1 gene (25). In addition, a peculiar response to experimental hypoxia has been demonstrated in the kidney, which may redistribute the pre-existing VEGF protein, rather than increase mRNA and protein synthesis (26).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, normal kidney showed diffuse expression of VEGF in all tubules of the renal cortex and medulla (20). However, proximal tubules in the human kidney exhibit only faint, if any, labeling of VEGF mRNA and VEGF protein when studied by in situ hybridization and immunohistochemistry (19,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, proximal tubules in the human kidney exhibit only faint, if any, labeling of VEGF mRNA and VEGF protein when studied by in situ hybridization and immunohistochemistry (19,20,21). Only one publication reported that human proximal tubular cells produced VEGF in culture (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific signaling pathway and downstream target genes activated by Etk are still elusive. Since VEGF has been shown to be a survival factor for epithelial cells (Kanellis et al, 2000) and is also upregulated by hypoxia (Jiang et al, 2000), we examined herein whether VEGF could be an Etk downstream target gene and whether Etk is involved in the signaling cascade that leads to the activation of VEGF expression in both normoxia and hypoxia conditions. Hence, Northern blot analyses were performed on total RNAs prepared from Pa-4 and Pa-4DEtk : ER cells.…”
Section: Induction Of Vegf Expression By Etk Activation In Pa-4detk :mentioning
confidence: 99%
“…Moreover, VEGF was found to stimulate DNA synthesis of endothelial cells preferentially through the same receptor, activating a distinct ERK1/2 pathway (Kanno et al, 2000), which was considered indispensable for the survival of endothelial cells (Gupta et al, 1999). Furthermore, these observations have recently been extended to renal tubular epithelial cells, suggesting that VEGF also promotes the survival of certain epithelial cells (Kanellis et al, 2000). Consequently, alterations in the expression and activity of VEGF have been postulated to play a crucial role in acquisition of the migrating and invasive tumorigenic properties of human malignant cells (Bagheri-Yarmand et al, 2001).…”
Section: Introductionmentioning
confidence: 95%